Designing the Foundation of a Multi-Tenant and Surrogate Key-Based Nusa Praja Village Government System on the Nusa Eka Platform - Sri Rahayu; Aulia Hamdi; Lina Nur Afifah; Aulia Suryaning Tyas; Rizki Cahya Putri; Mayza Nurul Khasanatun Nisa; Intan Nur Sifa; Purnia Setiawati (Yayasan Kita Menulis, 2026)
Village government administration in Indonesia is still largely manual, resulting in service inefficiencies and the potential loss of sensitive population data. The purpose of this research is to create the architectural foundation of a village government information system called NUSA PRAJA, which is part of the NUSAEKA multi-tenant Software as a Service (SaaS) platform. This research applies the Multi-Tenant Isolation concept to ensure data security and separation between villages, as well as the Surrogate Key concept to protect residents' National Identification Number (NIK) data from leaks. The research method used is Waterfall with the stages of requirements analysis, system architecture design, and database design. The results of the research are a multi-tenant system architecture design based on a shared database with tenant_id filters, an Entity Relationship Diagram (ERD) design with 14 main tables, and a flowchart design for three user roles. This project is expected to be a strong foundation for building a secure, scalable, and easy-to-use digital village system for village governments throughout Indonesia.